Arqueologia, Pré-história, Psicanálise: algumas considerações em torno da liberdade de saber - Jorge, Vítor Oliveria (Trabalhos de Antropologia e Etnologia, 2020)
A short “foray” into reflections on various disciplines for which the author, as an archaeologist, and in the attempt to be a better archaeologist, has passed and will continue to pass, trying to suggest the need to demystify some commonplaces that persist in academia, and that block knowledge.